Syntheses of 2-(6’-Fluorobenzothiazol-2’-ylamino)-4, 6-(disubstituted thiouriedo)-1,3-pyrimidine Derivatives as Antimicrobial Agents - Anoop K. Pathak; Viney Chawla; Shailendra K. Saraf (E-Journal of Chemistry)
A new series of 1,3-pyrimidine derivatives (3a-f) have been synthesized by reacting 2,4,6-Trichloropyrimidine with nucleophilic reagents 2-amino-6-fluorobenzothiazole (1) in the presence of acetone. The (4,6- dichloro-pyrimidin-2-yl)-amine (2) so produced was then reacted to two moles of phenylthiourea derivatives to yield title compounds (3a-f). The structural assessment of the compounds (3a-f) was made on the basis of spectral data. The synthesized compounds were screened for their in vitro growth inhibiting activity against different strains of bacteria viz., B. subtilis, E. coli, P. aeruginosa and S. aureus using agar diffusion technique. Compounds 3c and 3f exhibited highest antibacterial activity.